Audit Delay: Complexity of Company Size as Moderation Variable - Anggraeni, Galuh; Wulandari, Ika (University of Merdeka Malang, 2024)
In conducting the study, the aim was to be able to determine the influence of profitability, complexity of operations and financial distribution on the duration of the audit by using the size of the company as a moderation variable. The use of data is in the form of secondary data derived from the company's financial statements. This research was conducted on manufacturing companies listed on IDX or the Indonesia Stock Exchange in 2020-2022. In the selection of the sample, as many as 255 companies out of 85 companies were selected through selective sampling. The data analysis used in this study was in the form of multiple linear regression and moderated regression analysis (MRA) to test the influence of dependent variables and moderation. The results show that profitability and complexity of operations have a significant influence on the length of the audit. Financial distress can have a major impact on the length of the audit time. The size of the company moderates the effect of profitability on the duration of the audit, but the complexity of operations and financial distribution does not affect the duration of the audit.